2018
DOI: 10.1002/bmc.4301
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and residues of indoxacarb enantiomers in rice plants, rice hulls and brown rice using enriched S‐indoxacarb formulation and enantiopure formulation

Abstract: A chiral liquid chromatography-tandem high resolution mass spectroscopic method was developed for the analysis of indoxacarb enantiomers in rice plants, rice hulls and brown rice. Chiral separation of two enantiomers was carried out on a Superchiral S-OD column maintained at 20°C and eluted with 0.3 mL/min methanol. Samples were extracted by acetonitrile solution with ultrasound and cleansed by dispersive solid-phase extraction of 50 mg of primary secondary amine and 50 mg of C . This method was successfully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Indoxacarb can impair nerve function and cause loss of appetite, paralysis, or death of target pests such as lepidoptera, some homoptera, and coleoptera pests by blocking the sodium channel of the target neuron (Lapied et al 2001;Li et al 2018). Because of its insecticidal activity, indoxacarb is used for pest control in rice (Shi et al 2018), tea (Zhang et al 2014a(Zhang et al , 2015, fruits, vegetables, soybeans, alfalfa, peanuts, and other crops (Sun et al 2013); it is now registered and listed in more than 75 countries around the world, with global sales reaching $185 million in 2014 (Hua 2019). The average concentration of indoxacarb in surface water ranges from 3.7 to 7.8 μg/L, and the peak concentration is 13.7 μg/L (European Food Safety Authority et al 2018; Monteiro et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indoxacarb can impair nerve function and cause loss of appetite, paralysis, or death of target pests such as lepidoptera, some homoptera, and coleoptera pests by blocking the sodium channel of the target neuron (Lapied et al 2001;Li et al 2018). Because of its insecticidal activity, indoxacarb is used for pest control in rice (Shi et al 2018), tea (Zhang et al 2014a(Zhang et al , 2015, fruits, vegetables, soybeans, alfalfa, peanuts, and other crops (Sun et al 2013); it is now registered and listed in more than 75 countries around the world, with global sales reaching $185 million in 2014 (Hua 2019). The average concentration of indoxacarb in surface water ranges from 3.7 to 7.8 μg/L, and the peak concentration is 13.7 μg/L (European Food Safety Authority et al 2018; Monteiro et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The polysaccharide-derived CSP has been demonstrated to have a high potential for rapid chiral separation, with the two enantiomers of indoxacarb achieving baseline separation on Chiralpak AS-H, Superchiral S-OD and Chiralcel IG-3 chiral columns. [30][31][32] However, reports on the separation of DCJW on any chiral CSP do not exist. In this study, we used five polysaccharide-based CSPs (Superchiral S-OD, Chiralpak IH-3, Chiralpak IC, Chiralpak IB and Chiralpak IA) to separate the enantiomers of indoxacarb and DCJW under reversed-phase conditions.…”
Section: Development Of Methods For Quantitative Analysis 331 Chiral ...mentioning
confidence: 99%
“…The dissipation study on indoxacarb in rice [14] found that the half-lives of R-indoxacarb and S-indoxacarb were 4.20-4.33 and 3.45-3.57 d in rice straw. In this study, the half-lives of indoxacarb in rice husk and brown rice were 4.4-8.1 and 10.3-20.4 d, respectively, which inferred that indoxacarb dissipated faster in rice straw than in husk and brown rice.…”
Section: Residue Dissipation Studymentioning
confidence: 99%
“…The QuEChERS method was employed to determine indoxacarb in rice-related matrices by LC-MS/MS, in which the rice samples were cleaned up by N-propyl ethylene diamine (PSA) and Octadecylsilyl, ODS (C18), while the soil samples were not purified [13]. Besides, the degradation and residues of indoxacarb enantiomers were determined in rice using chiral liquid chromatography-tandem high-resolution mass spectrometry [14].…”
Section: Introductionmentioning
confidence: 99%